Applying Show And Tell Method To Enhance Student's Speaking Ability At Eight Grade Students Of SMP Singosari Delitua - Helmi Artini Damanik; Fenty Debora Napitupuluh (Jurnal Scientia, 2022)
This study related to students' speaking ability using the Show and Tell method at eighth grade students of SMP Singosari Delitua. The purpose of this research was to find out whether the show and tell method can enhance students' speaking ability. Population and sample of this research was eighth grade students of SMP Singosari Delitua. To achieve the research objectives, the researcher used classroom action as a method in this research. The researcher also used pre-test and posttest in assessing the result of speaking ability. The author uses two cycles. The results of this study was that the show and tell method can enhance students' speaking ability. This can be proven from the test calculations on both cycles. In the pre-test, the average score of students was 54.85. In the post-test, cycle I the average score of speaking ability was 72 and the average score in the post-test of cycle II was 82.85. Based on these data, it can be concluded that there was a significant increase in students' speaking ability by applying the show and tell method.Keywords: Applying, Show And Tell, Speaking